De novo repeat interruptions are associated with reduced somatic instability and mild or absent clinical features in myotonic dystrophy type 1. (November 2018) - Cumming, Sarah; Hamilton, Mark; Robb, Yvonne; Gregory, Helen; McWilliam, Catherine; Cooper, Anneli; Adam, Berit; McGhie, Josephine; Hamilton, Graham; Herzyk, Pawel; Tschannen, Michael; Worthey, Elizabeth; et al.
Abstract Myotonic dystrophy type 1 (DM1) is a multisystem disorder, caused by expansion of a CTG trinucleotide repeat in the 3′-untranslated region of theDMPK gene. The repeat expansion is somatically unstable and tends to increase in length with time, contributing to disease progression. In some individuals, the repeat array is interrupted by variant repeats such as CCG and CGG, stabilising the expansion and often leading to milder symptoms. We have characterised three families, each including one person with variant repeats that had arisen de novo on paternal transmission of the repeat expansion. Two individuals were identified for screening due to an unusual result in the laboratory diagnostic test, and the third due to exceptionally mild symptoms. The presence of variant repeats in all three expanded alleles was confirmed by restriction digestion of small pool PCR products, and allele structures were determined by PacBio sequencing. Each was different, but all contained CCG repeats close to the 3′-end of the repeat expansion. All other family members had inherited pure CTG repeats. The variant repeat-containing alleles were more stable in the blood than pure alleles of similar length, which may in part account for the mild symptoms observed in all three individuals. This emphasises the importance of somatic instability as a disease mechanism in DM1. Further, since patients with variant repeats may have unusually mild symptoms, identification of these individuals has important implications for genetic counselling and for patient stratification in DM1 clinical trials.